The Supervisory Role of the Board of Commissioners and Audit Committee on Compliance with Financial Instrument Risk Disclosure in Indonesian General Banking - Ramdani, Rahmat Fajar (Neolectura, 2024)
Banking is a corporate sector that has high financial risks on financial instruments so that complete and transparent disclosure of risk information is needed to increase stakeholder trust. The purpose of this study is to examine the role of the existence of the board of commissioners and audit committees on compliance with risk disclosure on financial instruments in the general banking sector in Indonesia. This study uses 46 non-sharia general banks listed on the Indonesia Stock Exchange for the period 2021 to 2023. This study uses the number of boards of commissioners and audit committees as a measure of the board of commissioners and audit committee variables, this study uses a financial risk disclosure index compiled based on PSAK 107. To test the research hypothesis using multiple linear regression analysis. The results of the study empirically prove that the existence of the board of commissioners and audit committee can significantly affect the level of financial risk disclosure on financial instruments in general banking in Indonesia so that it can be concluded that the role of supervision of the audit committee and board of commissioners is able to strengthen management compliance with the provisions of accounting standards according to PSAK applicable in Indonesia.